Experimental investigation on surface finish of drilled hole by TiAlN, TiN, AlCrN coated HSS drill under dry conditions. (2020) - Haja Syeddu Masooth, P.; Jayakumar, V.
Abstract: In this present study, the effect of three different coatings namely TiN, AlCrN, TiAlN under dry drilling conditions are examined to investigate the coated drills effect on the surface finish of the hole produced in AA5052. The surface roughness and cylindricity tests are conducted to measure the surface finish and hole profile respectively. The results obtained by the Field Emission Scanning Electron Microscopy (FESEM) and Energy dispersive spectroscopy (EDS) analysis indicate the elemental chemical composition of the tools used. Consequently, TiAlN coated drill had the significant effect on the surface substrate with less tool wear and excellent surface finish properties.